BY PSYCHOLOGISTS OF OUR COUNTRY STUDY OF STRESS IN ATHLETES - Radjabov A.A.; Murodullayeva Sh.O., (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article describes the causes of stress, the spheres of influence and the psychological characteristics that affect the performance of athletes.